PLATELET AGGREGATION IN VITRO ANALYSIS OF 67 kDa IMMUNOGENIC PROTEIN FRACTION FROM Aedes albopictus SALIVARY GLAND (SKUSE) (DIPTERA: CULICIDAE) - Rike Oktarianti; Syubbanul - Wathon; Intan Fitri Indrasari; Nadya Rismana Fitriani; Kartika Senjarini (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2020)
Cardiovascular disease is caused by impaired heart and blood vessel function. Coronary heart disease includes acute coronary syndrome due to narrowing of the coronary arteries. Aspirin is an anti-platelet drug which is commonly used for primary and secondary prevention of coronary heart disease. The effectiveness of aspirin has limitations because 10-20% of patients who use aspirin continue to experience vascular blockage. The haematophagus arthropods salivary glands contain apyrase which can inhibit platelet aggregation and thus a potential candidate for anti-platelet drug discovery. Our studies from salivary gland protein extract of Aedes albopictus found a 67 kDa protein fraction which has a similar molecular weight range from the previously identified apyrase of other mosquitoes vectors. The purpose of this study was to determine the apyrase potential capacity of 67 kDa protein fraction from salivary gland of Ae. albopictus. The present study employed inhibition percentage of platelet aggregation method in determining its apyrase activity. Aspirin was used as a positive control with 2 different concentrations of 0.1 mg/mL and 2 mg/mL. PBS 1mM pH 7.4 was used as a negative control treatment, while negative control without treatment only involved the addition of PRP and ADP. The inhibition percentage activity from the 67 kDa sample ranged from 3-37% whereas the total protein extract comprised of only 1%. The positive control of aspirin was 0.1 mg/mL and 2 mg/mL, resulting in inhibition percentage of 5% and 17%, respectively. The data showed that the inhibition percentage of platelet aggregation from protein 67 kDa is generally higher than those of total salivary gland protein extract as well as positive control. This indicated that the 67 kDa protein has a potential apyrase activity.